Resurrection of genus Phocanema Myers, 1959, as a genus independent from Pseudoterranova Mozgovoĭ, 1953, for nematode species (Anisakidae) parasitic in pinnipeds and cetaceans, respectively - Bao, M., Giulietti, L., Levsen, A.,; Karlsbakk, E. (Parasitology International, 2023)
Species of the genus Pseudoterranova, infect kogiid cetaceans and pinnipeds. However, there is mounting molecular evidence that those from cetaceans and pinnipeds are not congeneric. Here, we provide further evidence of the non-monophyly of members of Pseudoterranova from phylogenetic analyses of the conserved nuclear LSU rDNA gene, entire ITS rDNA region and mtDNA cox2 gene, and identify morphological characters that may be used to distinguish the members of the two clades. We propose the resurrection of the genus Phocanema, with Ph. decipiens (sensu stricto) as the type species, to encompass Ph. decipiens, Ph. azarasi, Ph. bulbosa, Ph. cattani and Ph. krabbei, all parasites of pinnipeds. We propose to restrict the conception of genus Pseudoterranova, which now harbours two species infecting kogiid whales; Ps. kogiae (type species) and Ps. ceticola. Members of the genera Phocanema and Pseudoterranova differ by the shape and orientation of the lips, relative tail lengths, adult size, type of final host (pinniped vs. cetacean) and phylogenetic placement based on nuclear rDNA and mtDNA cox2 sequences.